Negotiation approaches, initial position and choice of communication medium in solving environmental cases in Malaysia - Abdul Rahim, Norhayati Rafida (2016)
This study examines the relationship of negotiation approach, initial position and the use of communication medium among environmental control officers in solving environmental cases in Malaysia. Previous studies believe that negotiation is more efficient in a form of face-to-face (FtF) communication. Since conflict may be complicated at times, the use of communication medium is an advantage in order to reduce the gap of which may not be able to be provided by the traditional communication of FtF. The communication media are found to have communication patterns and managerial effectiveness. The new technology of communication is unable to replace FtF when FtF interactions offer richer communication and result in better outcomes. To what extent the negotiation approach determines the choice of the communication medium? Which communication medium that is mostly used in the negotiation? To what extent do the environmental control officers make it rational to choose the particular communication medium? Does the covariate variable of initial position exert influence towards the direction between the negotiation approach and the choice of communication medium? There are two approaches involved namely qualitative and quantitative. A qualitative approach refers to a preliminary study which uses interviews, as the first stage of the research process. The interviews are carried out with the Environmental Control (ECo) and Assistant Environmental Control Officers (AECo). The interviews gather information to be used in at the second stage by which a quantitative approach is employed. The quantitative approach refers to a survey which adopts a set of questionnaire and responses of 186 respondents are analyzed. The analysis includes descriptive, T-Test, Chi-Square Test and Analysis of Covariance (ANCOVA) using the Statistical Procedure for Social Sciences (SPSS). The analysis wishes to identify which negotiation approach that actually determines the choice made on the communication medium and whether or not the covariate variable of initial position exert influences in the dependency of negotiation approach (integrative or distributive) and the choice of communication medium. The findings reveal a significant dependency of integrative negotiation approach in the rationales of choosing FtF when there is an influence of initial position, which is at the problem-tosolve stage. The distributive approach of negotiation, on the other hand, makes it significantly rational to use letter/fax in solving the environmental case in Malaysia. No influence of initial position is found to be significant in this particular direction. Other communication medium is found insignificant to none of the approach used in the negotiation after taking into consideration the presence of initial positions respectively. The new communication medium such as short messaging system (SMS) and website have been found as insignificant. FtF remains as the richest type of communication medium and to be practiced by the environmental control officers specifically in solving the environmental case. As environmental case involves multi parties, the effective communication must be constantly exercised through enforcements and trainings. An extensive study may revisit the strength of new communication medium from various factors such as the context of study, the outcomes of negotiation and the understanding of the cases involved in the negotiation.